2007
DOI: 10.1080/08916930601083946
|View full text |Cite
|
Sign up to set email alerts
|

Allograft inflammatory factor-1 and its immune regulation

Abstract: The allograft inflammatory factor-1 (AIF-1) is a 17 kDa interferon-gamma (IFN-gamma) inducible Ca(2+)-binding EF-hand protein that is encoded within the HLA class III genomic region. Three proteins including ionized Ca(2+)-binding adaptor 1, microglia response factor-1, and daintain are identical with AIF-1. The expression of AIF-1 was mostly limited to the monocyte/macrophage lineage, and augmented by cytokines such as IFN-gamma. It was assumed that AIF-1 was a novel molecule involved in inflammatory response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 59 publications
0
36
0
Order By: Relevance
“…The AIF1 protein is involved in inflammatory responses, allograft rejection and macrophage regulation, 41 and has been implicated in T1D by functional studies, showing regulatory effects on insulin secretion in mice and accumulation in the pancreas of prediabetic Bio-Breeding (BB) rats. 42 Also, a number of studies have implicated this protein in other AIDs, 41 including a recent report showing that AIF1 may be crucial in the pathogenesis of rheumatoid arthritis.…”
Section: Confirmation Of Mhc Class I Associationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The AIF1 protein is involved in inflammatory responses, allograft rejection and macrophage regulation, 41 and has been implicated in T1D by functional studies, showing regulatory effects on insulin secretion in mice and accumulation in the pancreas of prediabetic Bio-Breeding (BB) rats. 42 Also, a number of studies have implicated this protein in other AIDs, 41 including a recent report showing that AIF1 may be crucial in the pathogenesis of rheumatoid arthritis.…”
Section: Confirmation Of Mhc Class I Associationsmentioning
confidence: 99%
“…The AIF1 protein is involved in inflammatory responses, allograft rejection and macrophage regulation, 41 and has been implicated in T1D by functional studies, showing regulatory effects on insulin secretion in mice and accumulation in the pancreas of prediabetic Bio-Breeding (BB) rats. 42 Also, a number of studies have implicated this protein in other AIDs, 41 including a recent report showing that AIF1 may be crucial in the pathogenesis of rheumatoid arthritis. 43 In addition to rs2259571, we observed an independent association of rs3132451 in the promoter of the same gene, but this result was most likely an artifact, both judging from the heterogeneity within each of the two individual DRB1-DQA1-DQB1 haplotypes the associations mapped to and the negative result in the T1DGC families.…”
Section: Confirmation Of Mhc Class I Associationsmentioning
confidence: 99%
“…In the present study, immunohistochemistry revealed that sinusoidal regions, but not hepatic cell regions, were the main source of AIF-1 in IR liver injury. Previous studies have indicated that inflammatory cytokines, such as IFN-g, IL-1b, and transforming growth factor (TGF)-b, are the most potent inducers of AIF-1 expression [3,[22][23][24]. Indeed, we discovered that AIF-1 levels paralleled IFN-g levels in rats after reperfusion, and in rat macrophages after stimulation with IFN-g and IL-1b, the expression of AIF-1 was up-regulated.…”
Section: Discussionmentioning
confidence: 59%
“…AIF-1 is produced by activated macrophages in transplant rejection and autoimmune disorders [16,17], and LYVE-1 is a marker for lymphatic endothelium which is also expressed by activated bone marrow and tissue macrophages [18]. FYB, also called ADAP (Adhesion and Degranulation Promoting Adaptor Protein), mediates signaling from T-cell antigen receptors to integrins, leading to enhanced cellular adhesion [19].…”
Section: Discussionmentioning
confidence: 99%